Análisis de los factores que inciden en la competitividad de las exportaciones del banano ecuatoriano en el periodo 2021 – 2023 - Arteaga Rivadeneira, Santiago Enrique (2023)
Exports and imports are essential factors for the economic growth and development of a nation, and competitiveness makes it possible to evaluate each of them. Capacity that a country has to dedicate itself to a particular area or industry, that is why this study is carried out, which aims to Examine the impact of Ecuadorian banana exports and their competitiveness in 2021-2023, since in recent years the item has been significant for the development of the country, despite having passed a pandemic.....